Assessing the effectiveness of information literacy integration in secondary school subjects: Perspectives from librarians - Oluwole Olumide Durodolu; Mojapelo, Samuel M; Oladokun, Bolaji David; Soyele, Esther K; Etuk, Anne Sam (Daluang: Journal of Library and Information Science, 2025)
Purpose. This study examines the role of school librarians in promoting information literacy in secondary schools within a metropolitan city. It highlights the importance of information literacy, which involves the ability to access, evaluate, and use information effectively. Methodology. The research, using qualitative interviews with librarians from six selected local government areas, investigates how librarians support teachers and enhance educational outcomes. Key research areas include methods used by librarians to determine teachers' information needs, the extent of consultation with teachers on new acquisitions, how librarians inform teachers about available resources, and the adequacy and usage frequency of library resources. Results and discussion. The findings reveal varying levels of librarian engagement, with some actively collaborating with teachers and others taking a more passive approach. Challenges identified include time constraints and resource inadequacies. Conclusions. The study emphasizes the need for better communication and resource management to support information literacy. Despite recognizing its importance, gaps exist in understanding effective librarian practices for empowering teachers and students. Recommendations include fostering librarian-teacher collaboration, updating resource collections, and increasing awareness of available resources to enhance their use in education.